2019
DOI: 10.3390/su11061647
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Dynamics of Intercity Technology Transfer Networks in China’s Three Urban Agglomerations: A Patent Transaction Perspective

Abstract: Technology transfer has become a vital pipeline for acquiring external knowledge. The purpose of this paper is to portray the spatial dynamics of intercity technology transfer networks in China’s three urban agglomerations based on patent right transaction data from 2008 to 2015. The integration of social networks and spatial visualization is used to explore spatial networks and influencing variables of the networks. The results demonstrate that Beijing, Shanghai, and Shenzhen are emerging as hubs in the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…The innovation value chain of patents research funding and human resource input significantly increased the number of SCI papers in universities [12].…”
Section: Plos Onementioning
confidence: 99%
“…The innovation value chain of patents research funding and human resource input significantly increased the number of SCI papers in universities [12].…”
Section: Plos Onementioning
confidence: 99%
“…Based on the patent transfer data of the State Intellectual Property Office from 2000 to 2015, Zhang et al [42] constructed China's inter-city technology transfer network, and the results showed that there was a certain geographical differentiation in China's inter-city technology transfer. Based on the patent transaction data of China's three major urban agglomerations from 2008 to 2015, Liu et al [43] analyzed the spatial structure and the temporal evolution of the three major urban agglomeration intercity network technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They occupied five seats, and they belong to the Beijing-Tianjin-Hebei and Yangtze River Delta regions of China. The three major urban agglomerations of Beijing-Tianjin-Hebei, the Yangtze River Delta, and the GBA are the most dynamic and innovative regions in China with technological proximity [43]. Fujian, Guangxi, Jiangxi, and Hunan are all at the forefront of technical exchanges with the GBA, and these four regions border Guangdong province, showing geographical proximity.…”
Section: Network Node Strength Analysismentioning
confidence: 99%
“…A city with a more competitive market structure or one that is not too large (a population less than 1 million) will also show a higher patent intensity. Liu et al (2019) analyzed the spatial dynamics of intercity technology transfer networks in China's three urban agglomerations based on patent right transaction data in 2008-2015 [26]. They found that Beijing, Shanghai, and Shenzhen are emerging as hubs in the three urban agglomerations.…”
Section: Introductionmentioning
confidence: 99%